Sexual offences and the law in Nigeria: an injustice to the female adolescent (1994)
In recent times, cases of sexual assaults on female adolescent girls is growing in prominence .This constitute a serious jeopardy to the adolescent girl in Nigeria . Under the Nigerian Laws, sexual offenses are extensively dealt with . The question however is the fairness of the law to the victim – the adolescent girl . This paper examines the law on some sexual offenses, the process of investigation and prosecution. These issues would be critically examined vis a vis the effect and fairness of the adolescent girl .Finally recommendation would be made on how the law can bring justice to the adolescent girl